Oakeshott, Iqbal and Islamic Concept of “Learning To Be Human” Through The Legacy of the Meanings: A comparative and Analytical Discourse - Dr. Muhammad Iqbal Shah (`, 2025)
This research comprises on the comparative and analytical views of Oakeshott and Iqbal with especial reference to Islamic teachings regarding the inheritance of meanings as the central theme of any philosophy of education. Oakeshott’s educational philosophy and his epistemology revolves around the concept of the inheritance of meanings and on this basis he wanted to create such a human being who is the real human being having awareness and knowledge of the purpose and existence of his very personality as well as an elevated human being instead of just a bipod creature of the animal kingdom. Iqbal’s point of view was to have a self-aware selfhood who is vicegerent of the Ultimate Ego or God Who is All-Knowing-Self and this was on the foundations of knowledge. Islam also emphasis on the same point when Quran mentions the creation of Adam and presents the reference of the First Oath of Alast when Adam was made to learn the Names and due to that quality He was exalted above the angels and due to that knowledge, God order the angels to prostrate before Adam. Thus learning the meanings of human inheritance is equal to ‘learning how to be human being’ in Oakeshott’s thought while this learning for Iqbal is the basic element of the Khudi or Self and in the same manner this very characteristic of learning the inheritance of meaning is the elementary qualification for to be the vicegerent of God on the earth. Consequently this idea should be pivot of any philosophy of education. Keyword: Aa’dmi, Ins’aan, Epistemology, Legacy of Meanings, Stages of Self, Vicegerent